2018
DOI: 10.2478/aiht-2018-69-3160
|View full text |Cite
|
Sign up to set email alerts
|

Removing aflatoxin M1 from milk with native lactic acid bacteria, centrifugation, and filtration

Abstract: In order to minimise human exposure to aflatoxin M1 (AFM1) the levels of this highly carcinogenic mycotoxin in milk, heat-treated milk, and other dairy products have been limited to <0.05 μg kg-1. However, its removal from dairy products presents a challenge for dairy producers, as commercial additives change organoleptic properties, and filtration alone yields poor results. The aim of this study was to find a strain of lactic acid bacteria (LAB) from milk or dairy products that most effectively binds AFM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…If the binding phenomenon is only temporary, the suitability as a food safety method will not be relevant due to the uncontrollable conditions and risks induced. Several studies have reported how different levels of aflatoxins are released from formed aflatoxin and LAB complex under different conditions [32,34,36,37,39,51,52].…”
Section: Challenges With Interpreting the Results Of Binding Aflatmentioning
confidence: 99%
See 1 more Smart Citation
“…If the binding phenomenon is only temporary, the suitability as a food safety method will not be relevant due to the uncontrollable conditions and risks induced. Several studies have reported how different levels of aflatoxins are released from formed aflatoxin and LAB complex under different conditions [32,34,36,37,39,51,52].…”
Section: Challenges With Interpreting the Results Of Binding Aflatmentioning
confidence: 99%
“…One factor to consider in the binding analysis is the stability of the bound complex. Even simple washing can release 20–70% of the initially categorized bound aflatoxins back to detectable forms [32,34,36,37,39,51,52]. The stability of the formed bond is an important factor to assess the suitability of binding agents in food systems to reduce the harmful effects of aflatoxins.…”
Section: Binding Of Aflatoxins As a Biocontrol Methodsmentioning
confidence: 99%
“…Their results indicated 100% of AFM1 in milk reduced to undetectable levels by SC or in combination with LAB at a level of 0.05 μg/L and 92% by SC at 1010 cell mL −1 at a level of 0.1 µg/L. Similarly, recent studies show the effectiveness of LAB and SC in the reduction of AFM1 [65] [66]. There is also evidence that the use of enzymes is potent in the reduction of AF.…”
Section: Treatment Of Afm1 In Milk and Milk Productsmentioning
confidence: 89%
“…The authors conclude that the use of S. cerevisiae immobilized with perlite may be a practical solution to address the problem of contamination of aflatoxins in dairy products. Kuharić et al (2018) selected, isolated and identified ten species of lactic acid bacteria from milk and dairy products with the objective to select a strain which binds more effectively to AFM 1 . In addition, they assessed whether the heat treatment of LAB would affect binding ability.…”
Section: Challenges and Implications Of Aflatoxin M 1 Methods Of Decomentioning
confidence: 99%
“…The authors reported that binding efficiency ranged from 21 to 92% for viable cells and from 26 to 94.5 for thermally treated cells. According to Kuharić et al (2018) although the mechanisms of action of lactic acid bacteria on aflatoxins has not yet been fully elucidated, some studies suggest that AFM 1 molecules bind physically to cell wall components, mainly polysaccharides and peptidoglycans, instead of creating covalent bonds with or being metabolized by lactic acid bacteria. In addition, they emphasize that the heat treatment seems to increase the binding surface for AFM 1 , providing not only the wall of the lactic acid bacteria cell, but also other components.…”
Section: Challenges and Implications Of Aflatoxin M 1 Methods Of Decomentioning
confidence: 99%